Iron–Cobalt-Based Materials: An Efficient Bimetallic Catalyst for Ammonia Synthesis at Low Temperatures - Rai, Rohit K; Al Maksoud, Walid; Morlanés, Natalia; Harb, Moussab; Ahmad, Rafia; Genovese, Alessandro; Hedhili, Mohamed N; Cavallo, Luigi; Basset, Jean-Marie (ACS catalysis, 2022)
Ammonia is one of the most commonly produced chemicals in the industry. As a result, ∼1–2% of the world’s electrical energy is used, and it produces ∼1.5–2% of global CO2 emissions. Therefore, developing efficient catalysts at milder conditions is highly desirable. Here, efficient iron/cobalt catalysts for ammonia synthesis are prepared with different Fe/Co ratios from phthalocyanine precursors, resulting in Fe–Co bimetallic nanoparticles embedded in a porous carbon–nitrogen matrix. The incorporation of Co to the Fe catalyst up to 20% wt of Co leads to ∼40% enhancement in the activity compared to the monometallic Fe-based catalyst. Interestingly, catalysts exhibit excellent activity even at low temperatures (350 °C). E a for the most efficient 6K–FePc80CoPc20 catalyst is found to be 29 kJ·mol–1, suggesting facile activation of N2 at low temperatures. An in-depth kinetic study revealed that introducing Co in the Fe catalysts drastically tuned the surface of the catalyst by weakening the various NH x retarding species. Density functional theory calculations confirm the thermodynamic feasibility for introducing 25% of Co at surface Fe sites. This indicates that the presence of Co on the surface draws negative charges from neighboring Fe sites, making the exposed Fe sites neutral and more favorable for N2 activation on the bimetallic K2O/Co–Fe catalyst and displaying a more thermodynamically feasible energy profile as compared to the pristine K2O/Fe catalyst.